Annotate the Web: Four Ways to Mark Up Web Content. Issue 1 (2nd January 2016) - Davis, Robin Camille
ABSTRACT: Web annotation has been a pipe dream almost since the birth of the Internet itself. Commenting in the margins of a text itself is so simple for paper and print, yet replicating the experience online remains elusive. In this article, I examine four tools for private or public web annotation. Hypothesis and Genius offer users a shareable way to annotate webpages line by line and start conversations in the margins. Pinboard and Evernote allow users to organize and save web documents and add private annotations.